Pelaksanaan Audit Keamanan Sistem Informasi Absensi Greatday Menggunakan Framework NIST - Wulantari, Nur Ayu; Sutabri, Tata (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The GreatDay attendance information system application is an attendance app that facilitates the automatic and real-time recording of employee attendance, both online and offline, with support for features such as facial recognition (Face Recognition). This study aims to evaluate the security of the GreatDay attendance information system using the NIST framework, which includes audit planning, system identification, risk assessment, implementation of security controls, and testing the effectiveness of controls. To ensure that the system functions optimally and securely, an information system security audit is needed using the NIST (National Institute of Standards and Technology) framework. NIST provides guidelines for auditing information system security to identify potential risks and threats, as well as to evaluate the implementation of appropriate security controls. Based on the results of this study, it can be concluded that the attendance information system is at level 3, indicating that the procedures and controls set by the institution have been implemented. This conclusion is based on the overall security audit assessment, which scored 3.7005 out of 5. Keywords: Attendance Information System, GreatDay, NIST, System Security, Audit, Face Recognition.